Cultural Tourism Business Management: A Fair and Sustainable Strategy Based on Local Participation and Digital Innovation for Indonesia's Cultural Image - MAHARANI, Ni Kadek Yulia; MAHARANI, Anak Agung Istri Nandita; NOVILIANTI, Ni Putu; PUTRI, Kadek Daniella Teja (Journal Management and Hospitality, 2025)
Cultural tourism is a vital sector that integrates travel with efforts to preserve cultural heritage and strengthen local identity, while simultaneously contributing to the growth of the creative economy and Indonesia’s cultural diplomacy. Beyond its economic value, cultural tourism serves as a medium for fostering appreciation of traditions and supporting the sustainable development of cultural assets. This paper aims to analyze fair and sustainable cultural tourism management strategies by emphasizing local community participation and digital innovation to enhance Indonesia’s cultural image. A literature review approach is applied, drawing upon theories, regulations, case studies, and best practices from various cultural destinations. The findings highlight that the Community-Based Tourism (CBT) model has proven effective in empowering local communities and preserving cultural heritage. Nevertheless, significant challenges remain, including the risks of cultural commodification and unequal distribution of economic benefits. To address these issues, the study recommends strengthening regulations, optimizing digital innovation, and fostering stakeholder synergy. These strategies are expected to establish cultural tourism governance that is fair, sustainable, and supportive of Indonesia’s cultural diplomacy in the global arena.